1994
DOI: 10.1017/s0021932000021489
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive careers of a cohort of men and women following an HIV-positive diagnosis

Abstract: This report examines the consequences of a positive HIV diagnosis upon the reproductive decision-making of 39 men and women in Scotland. Whilst the majority initially decide never to have any (more) children this sometimes changes as other factors gain ascendancy, such as a partner wanting 'their' child, and about one-third had had a child or were intending to do so. The motivations underlying such decisions are discussed and ways in which health services could intervene to support people with HIV in making re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Couples indicated that their reproductive health tended to be ignored or neglected by providers unless the couples were diagnosed with HIV infection during pregnancy. This finding is consistent with previous studies in the US showing that HIV‐positive women perceived that health care professionals were not willing to discuss reproductive options with them, assumed they did not have sexual lives, or discouraged them from continuing childbearing (Bruyn, 2002; Green, 1994; Sowell & Misener, 1997). Couples in this study actively searched for information that would help them make their own decisions about their pregnancies.…”
Section: Discussionsupporting
confidence: 91%
“…Couples indicated that their reproductive health tended to be ignored or neglected by providers unless the couples were diagnosed with HIV infection during pregnancy. This finding is consistent with previous studies in the US showing that HIV‐positive women perceived that health care professionals were not willing to discuss reproductive options with them, assumed they did not have sexual lives, or discouraged them from continuing childbearing (Bruyn, 2002; Green, 1994; Sowell & Misener, 1997). Couples in this study actively searched for information that would help them make their own decisions about their pregnancies.…”
Section: Discussionsupporting
confidence: 91%
“…O ur previous research had explored attitud es toward s sex and reproduction am ong young heterosexual m en and wom en (W ight, 1993; K itzinger, 1995) and people with H IV (Green, 1994). In the light of th is wo rk, we becam e interested in interviewing wom en seeking sperm .…”
Section: The Theoretical Background and Development Of The Research Qmentioning
confidence: 99%
“…W ight' s work with young m en from a working class locality of G lasgow dem onstrate d that HIV was not an issue in th eir reproductive decisions and that, in any case, they tended to assum e that only certain typ es of people (such as`slags' and`junkies' ) were liable to be infected (W ight, 1993; see also M aticka-T yndale, 1992; and W oodcock et al, 1992). G reen' s research show ed that, even given the risk of H IV transm ission, som e people in long-te rm com m itted relationships were willing to go ahead and try to conceive with their H IV-positive partners because they speci® cally wanted to have their child (Green, 1994). O ther research has show n how the value of personal relationships, such as group solidarity or affection and trust betw een partners, often overrides concern with H IV infection (e.g.…”
Section: The Theoretical Background and Development Of The Research Qmentioning
confidence: 99%
See 2 more Smart Citations